Given a function f that satisfies the equation ( x + 2 ) ( x + 1 ) f ( x + 2 ) + ( x + 1 ) f ( x + 1 ) + f ( x ) = 0 Find the maximum number of real zeros of the function g ( x ) = ( x + 1 ) ( x + 2 ) ( x + 3 ) ( x + 4 ) ( x + 5 ) ( x + 6 ) f ( x + 6 ) − 2 ( x + 1 ) ( x + 2 ) ( x + 3 ) f ( x + 3 ) + f ( x ) + 2 0 1 8 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution!
Let us define the shift operator and the identity operator in the following way: T f ( x ) = f ( x + 1 ) and I f ( x ) = f ( x ) , respectively. Then the given functional equation can be written in the form ( ( x + 2 ) ( x + 1 ) T 2 + ( x + 1 ) T + I ) f ( x ) = 0 . If you apply the operator ( x + 1 ) T − I to both sides of the previous equation, we get the equation ( ( x + 1 ) ( x + 2 ) ( x + 3 ) T 3 − I ) f ( x ) = 0 . Now applying the operator ( x + 1 ) ( x + 2 ) ( x + 3 ) T 3 − I ) to both sides of the last equation, we get the equation ( ( x + 1 ) ( x + 2 ) ( x + 3 ) ( x + 4 ) ( x + 5 ) ( x + 6 ) T 6 − 2 ( x + 1 ) ( x + 2 ) ( x + 3 ) T 3 + I ) f ( x ) = 0 . Therefore, the expression ( x + 1 ) ( x + 2 ) ( x + 3 ) ( x + 4 ) ( x + 5 ) ( x + 6 ) f ( x + 6 ) − 2 ( x + 1 ) ( x + 2 ) ( x + 3 ) f ( x + 3 ) + f ( x ) must be equal to zero for all possible values of x . Then, the function g ( x ) has not real zeros. Thus the answer to the problem is 0 .
Problem Loading...
Note Loading...
Set Loading...
Define f k ( x ) : = ( x + 1 ) ( x + 2 ) … ( x + k ) f ( x + k ) for k > 0 . Then the given equation can be written f 2 ( x ) + f 1 ( x ) + f ( x ) = 0 , or equivalently f 2 ( x ) = − f 1 ( x ) − f ( x ) . Replacing x with x + k and then multiplying throughout by ( x + 1 ) … ( x + k ) , we have that for k > 2 , f k ( x ) = − f k − 1 ( x ) − f k − 2 ( x ) .
Therefore:
g ( x ) = f 6 ( x ) − 2 f 3 ( x ) + f ( x ) + 1 / 2 0 1 8
= − f 5 ( x ) − f 4 ( x ) − 2 f 3 ( x ) + f ( x ) + 1 / 2 0 1 8
= f 4 ( x ) + f 3 ( x ) − f 4 ( x ) − 2 f 3 ( x ) + f ( x ) + 1 / 2 0 1 8
= − f 3 ( x ) + f ( x ) + 1 / 2 0 1 8
= f 2 ( x ) + f 1 ( x ) + f ( x ) + 1 / 2 0 1 8
= 1 / 2 0 1 8
for all real x , so g ( x ) has no real zeros.